COMPARATIVE ANALYSIS OF AUTHENTIC LEADERSHIP MEASUREMENT TOOLS IN A SMALL BUSINESS CASE STUDY - László KOLLÁR; Anita PIEROG (Oradea Journal of Business and Economics)
According to international literature, managers who adopt a positive leadership style indicate a number of characteristics that are beneficial to the business organization, both in terms of individual and organizational performance. However, the conscious emergence and diffusion of these styles in the entrepreneurial sphere, as well as their research at the academic level in the Carpathian Basin, is still in its infancy. The aim of this study is to go beyond a general description of the styles and to explore the possibilities of their practical application, including their measurability. In this paper, we compare the measurement instruments (questionnaires) of authentic leadership presented in the literature using a comparative analysis method, and we also evaluate the measurement instruments under study by means of measurements carried out in a Hungarian company. The comparison will identify which measurement instruments, both from the literature and from the empirical point of view, could be applicable for a future larger sample study.